(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Various studies have highlighted different urban problems that have affected the quality of life of the urban dwellers in both developed and developing nations due to rapid socio - economic changes and increase in population. The aim of this study is to assess the perceived indicators of quality of life, so as to evolve strategy of upgrading the decayed urban communities. The multistage sampling method was adopted as a sampling technique. The following settlement were selected for the study, Down Quarters, Kurmin Gwari and Badarawa-Kwaru because of its slum like settlement. A total of 406 household’s heads/members were served with questionnaires, while 380 were returned and properly filled. Twelve (12) key informants were also interviewed in all the selected communities. The results show that more than three quarter of respondents get their water from hand dug well (M= 4.2151), and a little less than one quarter admitted to get water from Pipe borne, boreholes (M= 1.4272) and other sources. The study concluded that due to high population concentration of people, government could not provide the necessary amenities and services required by the teeming population therefore, the available ones were over stretched and became dilapidated and decay set in. The study recommends that the government of Kaduna state should embark on urban renewal which will prevent decay, clear areas bad areas, upgrade building, facilities and expand metropolis roads.